Factors associated with past 30-day abstinence from cigarette smoking in adult established smokers who used a JUUL vaporizer for 6 months - Christopher Russell; Farhana Haseen; Neil McKeganey (BMC, 2019)
Abstract Background JUUL is the fastest growing and highest selling brand of e-cigarette/vapor products in the USA. Assessing the effect of JUUL vapor products on adult smokers' use of conventional tobacco cigarettes can help inform the potential population health impact of these products. Methods Participants were 15,456 US adult established current smokers aged 21 years who had purchased their first JUUL Starter Kit from a retail store or online within the past 7 days. Online surveys assessed past 30-day use of conventional cigarettes, JUUL vapor products, and other e-cigarettes/vapor products at 3 and 6 months after their first JUUL purchase. Logistic regression models examined factors associated with smokers' odds of self-reporting past 30-day abstinence from cigarette smoking at 6 months. Results Past 30-day point prevalence abstinence from smoking at 6 months was 31.6% in the intent-to-treat (ITT) sample and 54.0% among those who responded at 6 months (n = 9040; 58.5% of ITT). Consecutive past 30-day smoking abstinence outcomes at 3 and 6 months were reported by 20.3% of the ITT sample and 40.6% of responders to both assessments (n = 7726). Covariate-adjusted odds for reporting past 30-day smoking abstinence at 6 months were significantly higher among primary users of mint- or mango-flavored JUULpods (compared to primary users of Virginia tobacco-flavored JUULpods), exclusive users of JUULpods in characterizing flavors (compared to exclusive users of tobacco-flavored JUULpods), daily users of the JUUL vaporizer (compared to less-than-daily), initial retail purchasers (compared to initial e-commerce purchasers), and those who first purchased a JUUL to help to quit smoking completely. Odds for reporting past 30-day smoking abstinence were significantly lower among those who, at study enrolment, had smoked regularly for ≥ 20 years, smoked ≥ 10 cigarettes per day, and smoked on all 30 of the previous 30 days. Conclusions Around one third of enrolled smokers and one half of smokers who responded to a 6-month follow-up reported being past 30-day abstinent from cigarette smoking after using a JUUL vaporizer for 6 months. More frequent use of a JUUL vaporizer and primary use of JUULpods in characterizing flavors, particularly mint and mango, appeared to be important to smokers' chances of quitting. The impact of suspending retail sales of flavored JUULpods on adult smokers' likelihood of quitting should be closely assessed.